Pembelajaran tematik berbasis kontekstual di SD Muhammadiyah 9 Malang - Efi Nilasari; Yudha Adrian; Ratno Susanto (Jurnal Teori dan Praksis Pembelajaran IPS, 2018)
This study aims to: (1) describe contextual-based thematic learning plan that is implemented in Muhammadiyah Primary School 9 Malang, (2) to describe contextual contextual teaching-learning in elementary school Muhammadiyah 9 Malang; (3) to describe contextual based thematic learning evaluation in Muhammadiyah Primary School 9 Malang. Methods This study is a qualitative descriptive study that describes phenomena in the field without treatment. The object of this research is the students of grade V SD Muhammadiyah 9 Malang. Sources of data obtained from teachers and students of class V. In addition, learning tools used when the implementation of learning. Main techniques of data collection through observation, documentation and interviews as research support techniques. Data analysis techniques used are data reduction, data display and conclusion / verification. The results showed that contextual thematic learning planning at SD Muhammadiyah 9 Malang was good enough and run as it should be. Implementation of contextually thematic learning at SD Muhammadiyah 9 Malang still not in accordance with the planning. The practice of contextual approach to thematic learning is still less than optimal. This is because teachers are less well understood with the application of contextual based thematic approach. Finally, the implementation of thematic learning evaluation that is used is in accordance with the assessment standards used. Evaluation of learning that includes assessment of student learning outcomes that include aspects of attitude, knowledge and skills.DOI: 10.17977/um022v3i12018p019